2014
DOI: 10.1242/jcs.150706
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis unveils a FANCA-modulated neddylation pathway involved in CXCR5 membrane targeting and cell mobility

Abstract: The aim of this study was to identify novel substrates of the FANCcore complex, the inactivation of which leads to the genetic disorder Fanconi anemia, which is associated with bone marrow failure, developmental abnormalities and a predisposition to cancer. Eight FANC proteins participate in the nuclear FANCcore complex, which functions as an E3 ubiquitin-ligase that monoubiquitylates FANCD2 and FANCI in response to replicative stress. Here, we use mass spectrometry to compare proteins from FANCcore-complexdef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
1
19
1
Order By: Relevance
“…Probably, both migration and invasiveness are independent from the DDR activity of the pathway, but, more realistically, linked to the recently reported FANCA loss-of-function-associated defect in CXCR5 neddylation, which decreases the membrane localisation of this receptor involved in cell motility, invasion and homing26. Clearly, our data indicate that the FANC proteins have a central role in melanoma development, favouring growth, motility, invasiveness and DNA damage resistance of melanoma cells.…”
Section: Discussionsupporting
confidence: 56%
“…Probably, both migration and invasiveness are independent from the DDR activity of the pathway, but, more realistically, linked to the recently reported FANCA loss-of-function-associated defect in CXCR5 neddylation, which decreases the membrane localisation of this receptor involved in cell motility, invasion and homing26. Clearly, our data indicate that the FANC proteins have a central role in melanoma development, favouring growth, motility, invasiveness and DNA damage resistance of melanoma cells.…”
Section: Discussionsupporting
confidence: 56%
“…Further analysis showed that CXCR5 is NEDDylated but Printed in Great Britain not ubiquitinated on lysine 339. The role of CXCR5 NEDDylation is to promote the membrane localisation of the receptor and is required for cell motility, a process controlled by CXCR5 in B-lymphocytes upon its ligand binding (Renaudin et al 2014).…”
Section: Membrane Receptorsmentioning
confidence: 99%
“…In DT40, cell line mutations of FANC complex proteins lead to inactivating of FANCC and USP1 without affecting FANCD2 ubiquitylation. These results suggesting FANC complex proteins may have a significant role in the DNA damage response and other cellular functions interpedently of FANCD2/FANCI ubiquitylation [13,14].…”
Section: Ubiquitylation and Deubiquitylation Of Fanc Pathwaymentioning
confidence: 85%
“…This process is crucial for recycling of the ID molecules while the ubiquitylated and nonubiquitylated forms are necessary for normal cellular function. USP1 seems to be enzyme involved in deubiquitylating procedure [13,14].…”
Section: Ubiquitylation and Deubiquitylation Of Fanc Pathwaymentioning
confidence: 99%
See 1 more Smart Citation